The Criminal Justice System in the Lithuanian SSR: Genesis, Specifics and Relationship with Unarmed Anti-soviet Resistance - Kareniauskaitė, Monika (Genocidas ir rezistencija, 2024)
The article analyses the criminal justice system of Soviet Lithuania: the formation of the system, its norms and institutions, the aggregate of laws, and the prosecution of criminals. It also reveals how the transformation of the Soviet regime after Stalin’s death was reflected in the legal reality. The dimension of political crime, criminal prosecution for various forms of resistance against the Soviet regime, is particularly emphasised.The research revealed that although after Stalin’s death the Soviet regime in Lithuania released its grip and Soviet law acquired more liberal features, it continued to be used for reprisals against people who espoused different opinions. Several features were characteristic to the criminal prosecution of those who participated in unarmed opposition and dissidents in the Lithuanian SSR: a) the suspect was accused of a political crime under an article of the Criminal Code applicable to his activities (such cases violated international law, but were legal in the Soviet legal system), b) political crimes were criminalised by interpreting articles of the Criminal Code too liberally (even in the Soviet system such cases lacked objectivity), c) political cases were masked by criminal offenses and also contained elements of non-political crimes (cases were not objective and criminal charges were falsified).Even in the late Soviet period, the Soviet legal system collaborated hand in hand with the Lithuanian Communist Party and the KGB and was an integral part of the Soviet ruling system. The dishonesty of the Soviet legal system often served as evidence that the criticism of the regime by dissidents was justified. The fact that Soviet authorities did not always follow the legal norms that regulated their own activities showed that legal reality in the USSR was just fiction. The regime, which became softer externally, continued to observe the same totalitarian logic internally.
Keywords: occupational regime; soviet law; unarmed resistance; repressions